Menelisik Kisah Nabi Adam dalam Tafsir Ibnu Katsir dan Tafsir Al-Misbah - rizqi, Rizqi Asfianudin; A.M Ismatullah (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2024)
Prophet Adam was the first human on earth, and as Muslims, we are obliged to believe in the existence of Prophets and Apostles because they are part of a series of pillars of faith. In the Koran, many verses mention the story of the Prophet Adam. The author found several variations of interpretation in the story of the Prophet Adam, such as the location of the heaven he visited, the name of the tree or fruit that was forbidden, the earth where he was sent down, wisdom, and the sentence of repentance given by Allah SWT, this is what prompted the author to carry out deeper research. This research uses a library research method and is maudhu'i or thematic based. This research aims to reveal the interpretations of Ibn Katsir and Quraish Shihab regarding the story of the Prophet Adam in the Koran and examine the similarities and differences contained in the two books of interpretation. The results of this research are that the interpretation of the verses of the story of the Prophet Adam by Ibn Katsir and Quraish Shihab has many differences and few similarities.